Molecular Variation and Phylogeny within Fusarium avenaceum and Related Species - Yli-Mattila Tapani; Abbas Asmaa; Gavrilova Olga; Gagkaeva Tatiana (MDPI, 2022)
Many recent articles feature research on the Fusarium tricinctum species complex (FTSC), and their authors present different ideas on how the isolates of this species complex can be identified at the species level. In previous studies, our aim was to investigate the phylogeny of FTSC strains, which researchers have morphologically identified as Fusarium avenaceum, Fusarium arthrosporioides, and Fusarium anguioides. In the current study, our phylogenetic maximum parsimony and likelihood analyses of the DNA sequences of the translation elongation factor 1-alpha (TEF1) and combined sequences of TEF1 and beta-tubulin (TUB2) supported the existence of at least four main groups among these strains. Main Group I mainly contains F. avenaceum strains, while Main Group II contains two subgroups, one of which primarily includes F. arthrosporioides strains, and the other mainly includes European F. anguioides strains. Main Group III contains strains from different plants that originated from Asia, including two F. anguioides strains. F. avenaceum strains, which are mostly isolated from different trees, form Main Group IV. A fifth group (Main Group V) was only supported by TEF1 sequences. The main groups previously found by us based on TUB2 sequences could be connected to the new species of the FTSC, which were identified based on TEF1 sequences. In addition, we found strains that significantly differ from Main Groups I-V, and we grouped some of them as single, intermediate, or sister groups. All of the main groups of the present work, and some single and intermediate strains, may represent different species of the FTSC, while the two subgroups of Main Group II constitute intraspecific variation. Regardless of whether they belonged to the main groups, all the analysed strains were able to form different enniatins and 2-amino-14,16-dimethyloctadecan-3-ol, but did not produce beauvericin.